Comparison of C2 dome-like laminectomy with C2 partial laminectomy for upper cervical ossification of the posterior longitudinal ligament - Miao, Dazhuang; Gao, Xianda; Zhen, Zihao; Yang, Dalong; Wang, Hui; Ding, Wenyuan (Frontiers in Surgery, 2023)
Objective To compare surgical outcomes of C2 dome-like laminectomy with C2 partial laminectomy in patients with ossification of the posterior longitudinal ligament (OPLL) up to the C2 level and above. Methods 32 patients underwent surgical treatment for OPLL up to C2 and were divided into: C2 dome-like laminectomy group (C2-DOM group, n = 16) and C2 partial laminectomy group (C2-PL group, n = 16). The cervical curvature (CCI), dura width at C2/3, Japanese orthopedic association (JOA) score, recovery rate (RR), neck disability index (NDI) score, and visual analogue scale (VAS) score were evaluated and compared preoperatively and postoperatively at 1 month, 3 months, 6 months, 1 year, and annually thereafter. Results The JOA score and NDI significantly improved at the final follow-up in both groups with no significant intergroup differences. There were no significant differences in preoperative dura width at C2/3 and VAS between the two groups. At the final follow-up, dura width at C2/3 in the C2-PL group was significantly larger than the C2-DOM group, while the VAS of C2-DOM group was significantly lower than C2-PL group. The CCI in both groups decreased compared with before surgery, and there was no significant difference in CCI between the two groups. Conclusion C2-DOM is less demolitive and reduces postoperative neck pain, while C2-PL can achieve more adequate decompression without increasing the risk of postoperative cervical kyphosis.